Can ammonia tolerance amongst lichen functional groups be explained by physiological responses? - Munzi, S; Cruz, C; Branquinho, C; Pinho, P; Leith, I D; Sheppard, L J (Environmental pollution (Barking, Essex : 1987), 2014)
Ammonia (NH3) empirical critical levels for Europe were re-evaluated in 2009, based mainly on the ecological responses of lichen communities without acknowledging the physiological differences between oligotrophic and nitrophytic species. Here, we compare a nitrogen sensitive lichen (Evernia prunastri) with a nitrogen tolerant one (Xanthoria parietina), focussing on their physiological response (Fv/Fm) to short-term NH3 exposure and their frequency of occurrence along an NH3 field gradient. Both frequency and Fv/Fm of E. prunastri decreased abruptly above 3 μg m(-3) NH3 suggesting direct adverse effects of NH3 on its photosynthetic performance. By contrast, X. parietina increased its frequency with NH3, despite showing decreased capacity of photosystem II above 50 μg m(-3) NH3, suggesting that the ecological success of X. parietina at ammonia-rich sites might be related to indirect effects of increased nitrogen (NH3) availability. These results highlight the need to establish NH3 critical levels based on oligotrophic lichen species.
Keywords: Critical levels; Environmental protection policy; Evernia prunastri; nitrogen; Xanthoria parietina

Current ozone levels threaten gross primary production and yield of Mediterranean annual pastures and nitrogen modulates the response - Calvete-Sogo, Héctor; Elvira, Susana; Sanz, Javier; González-Fernández, Ignacio; García-Gómez, Héctor; Sánchez-Martín, Laura; Alonso, Rocío; Bermejo-Bermejo, Victoria (Atmospheric Environment, 2014)
Pastures are among the most important ecosystems in Europe considering their biodiversity and distribution area. However, their response to increasing tropospheric ozone (O3) and nitrogen (N) deposition, two of the main drivers of global change, is still uncertain. A new Open-Top Chamber (OTC) experiment was performed in central Spain, aiming to study annual pasture response to O3 and N in close to natural growing conditions. A mixture of six species of three representative families was sowed in the field. Plants were exposed for 40 days to four O3 treatments: filtered air, non-filtered air (NFA) reproducing ambient levels and NFA supplemented with 20 and 40 nl l-1 O3. Three N treatments were considered to reach the N integrated doses of “background”, +20 or +40 Kg N ha-1. Ozone significantly reduced green and total aboveground biomass (maximum reduction 25%) and increased the senescent biomass (maximum increase 40%). Accordingly, O3 decreased community Gross Primary Production due to both a global reduction of ecosystem CO2 exchange and an increase of ecosystem respiration. Nitrogen could partially counterbalance O3 effects on aboveground biomass when the levels of O3 were moderate, but at the same time O3 exposure reduced the fertilization effect of higher N availability. Therefore, O3 must be considered as a stress factor for annual pastures in the Mediterranean areas.
Keywords: annual grasslands interactions; Critical levels; Dehesa; Global change; nitrogen; tropospheric ozone

Critical loads of nitrogen deposition and critical levels of atmospheric ammonia for semi-natural Mediterranean evergreen woodlands - Pinho, P; Theobald, M R; Dias, T; Tang, Y S; Cruz, C; Martins-Loução, M a.; Máguas, C; Sutton, M; Branquinho, C (Biogeosciences, 2012)
Nitrogen (N) has emerged in recent years as a key factor associated with global changes, with impacts on biodiversity, ecosystems functioning and human health. In order to ameliorate the effects of excessive N, safety thresholds such as critical loads (deposition ﬂuxes) and levels (concentrations) can be established. Few studies have assessed these thresholds for semi-natural Mediterranean ecosystems. Our objective was therefore to determine the critical loads of N deposition and long-term critical levels of atmospheric ammonia for semi-natural Mediterranean evergreen woodlands. We have considered changes in epiphytic lichen communities, one of the most sensitive comunity indicators of excessive N in the atmosphere. Based on a classiﬁcation of lichen species according to their tolerance to N we grouped species into response functional groups, which we used as a tool to determine the critical loads and levels. This was done for a Mediterranean climate in evergreen cork-oak woodlands, based on the relation between lichen functional diversity and modelled N deposition for critical loads and measured annual atmospheric ammonia concentrations for critical levels, evaluated downwind from a reduced N source (a cattle barn). Modelling the highly signiﬁcant relationship between lichen functional groups and annual atmospheric ammonia concentration showed the critical level to be below 1.9 µg m−3 , in agreement with recent studies for other ecosystems. Modelling the highly signiﬁcant relationship between lichen functional groups and N deposition showed that the critical load was lower than 26 kg (N) ha−1 yr−1 , which is within the upper range established for other semi-natural ecosystems. Taking into account the high sensitivity of lichen communities to excessive N, these values should aid development of policies to protect Mediterranean woodlands from the initial effects of excessive N.
Keywords: atmospheric ammonia; Critical levels; Critical loads; lichen functional-groups; Mediterranean evergreen woodlands (voyant); n deposition

Responses of evergreen and deciduous Quercus species to enhanced ozone levels. - Calatayud, Vicent; Cerveró, Júlia; Calvo, Esperanza; García-Breijo, Francisco-José; Reig-Armiñana, José; Sanz, María José (Environmental pollution (Barking, Essex : 1987), 2011)
Plants of one evergreen oak (Quercus ilex) and three deciduous oaks (Q. faginea, with small leaves; Q. pyrenaica and Q. robur, with large leaves) were exposed both to filtered air and to enhanced ozone levels in Open-Top Chambers. Q. faginea and Q. pyrenaica were studied for the first time. Based on visible injury, gas exchange, chlorophyll content and biomass responses, Q. pyrenaica was the most sensitive species, and Q. ilex was the most tolerant, followed by Q. faginea. Functional leaf traits of the species were related to differences in sensitivity, while accumulated ozone flux via stomata (POD1.6) partly contributed to the observed differences. For risk assessment of Mediterranean vegetation, the diversity of responses detected in this study should be taken into account, applying appropriate critical levels.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 20974507
Keywords: Anatomy; Critical levels; Functional leaf traits; Ozone; photosynthesis; Stomatal conductance

Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D; Büker, Patrick; Ashmore, Mike R (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata

Assessing the risk caused by ground level ozone to European forest trees: a case study in pine, beech and oak across different climate regions. - Emberson, Lisa D.; Büker, Patrick; Ashmore, Mike R. (Environmental pollution (Barking, Essex : 1987), 2007)
Two different indices have been proposed for estimation of the risk caused to forest trees across Europe by ground-level ozone, (i) the concentration based AOT40 index (Accumulated Over a Threshold of 40 ppb) and (ii) the recently developed flux based AFstY index (Accumulated stomatal Flux above a flux threshold Y). This paper compares the AOT40 and AFstY indices for three forest trees species at different locations in Europe. The AFstY index is estimated using the DO(3)SE (Deposition of Ozone and Stomatal Exchange) model parameterized for Scots pine (Pinus sylvestris), beech (Fagus sylvatica) and holm oak (Quercus ilex). The results show a large difference in the perceived O(3) risk when using AOT40 and AFstY indices both between species and regions. The AOT40 index shows a strong north-south gradient across Europe, whereas there is little difference between regions in the modelled values of AFstY. There are significant differences in modelled AFstY between species, which are predominantly determined by differences in the timing and length of the growing season, the periods during which soil moisture deficit limits stomatal conductance, and adaptation to soil moisture stress. This emphasizes the importance of defining species-specific flux response variables to obtain a more accurate quantification of O(3) risk.
The following values have no corresponding Zotero field: accession-num: 17412465
Keywords: Beech (Fagus sylvatica); Critical levels; Deposition; Flux; Forests; Holm oak (Quercus ilex); Ozone; Scots pine (Pinus sylvestris); stomata

Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. - Ferretti, M.; Fagnano, M.; Amoriello, T.; Badiani, M.; Ballarin-Denti, A.; Buffoni, A.; Bussotti, F.; Castagna, A.; Cieslik, S.; Costantini, A.; De Marco, A.; Gerosa, G.; et al. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.
The following values have no corresponding Zotero field: accession-num: 16889878
Keywords: AOTx; Critical levels; Effects; Mediterranean Region; Ozone; Stomatal flux

Measuring, modelling and testing ozone exposure, flux and effects on vegetation in southern European conditions--what does not work? A review from Italy. - Ferretti, M; Fagnano, M; Amoriello, T; Badiani, M; Ballarin-Denti, A; Buffoni, A; Bussotti, F; Castagna, A; Cieslik, S; Costantini, A; De Marco, A; Gerosa, G; et al. (Environmental pollution (Barking, Essex : 1987), 2007)
Ozone (O3) exposure at Italian background sites exceeds UN/ECE concentration-based critical levels (CLe(c)), if expressed in terms of AOT40. Yet the occurrence of adverse effects of O3 on forests and crops is controversial. Possible reasons include (i) ability of response indicators to provide an unbiased estimate of O3 effects, (ii) setting of current CLe(c) in terms of cut-off value and accumulation level, (iii) response functions adopted to infer a critical level, (iv) environmental limitation to O3 uptake and (v) inherent characteristics of Mediterranean vegetation. In particular, the two latter points suggest that critical levels based on accumulated stomatal flux (CLe(f)) can be a better predictor of O3 risk than CLe(c). While this concept is largely acknowledged, a number of factors may limit its applicability for routine monitoring. This paper reviews levels, uptake and vegetation response to O3 in Italy over recent years to discuss value, uncertainty and feasibility of different approaches to risk assessment.
Keywords: AOTx; Critical levels; Effects; Mediterranean Region; Ozone; Stomatal flux

Stomatal conductance of semi-natural Mediterranean grasslands: implications for the development of ozone critical levels. - Alonso, R; Bermejo, V; Sanz, J; Valls, B; Elvira, S; Gimeno, B S (Environmental pollution (Barking, Essex : 1987), 2007)
Intra-genus and intra-specific variation and the influence of nitrogen enrichment on net assimilation and stomatal conductance of some annual Trifolium species of Mediterranean dehesa grasslands were assessed under experimental conditions. Also gas exchange rates were compared between some Leguminosae and Poaceae species growing in the field in a dehesa ecosystem in central Spain. The results showed that the previously reported different O3 sensitivity of some Trifolium species growing in pots does not seem to be related to different maximum g(s) values. In addition, no clear differences on gas exchange rates could be attributed to Leguminosae and Poaceae families growing in the field, with intra-genus variation being more important than differences found between families. Further studies are needed to increase the database for developing a flux-based approach for setting O3 critical levels for semi-natural Mediterranean species.
Keywords: Critical levels; Grasslands; Ozone; Semi-natural vegetation; Stomatal conductance

Stomatal conductance of semi-natural Mediterranean grasslands: implications for the development of ozone critical levels. - Alonso, R.; Bermejo, V.; Sanz, J.; Valls, B.; Elvira, S.; Gimeno, B. S. (Environmental pollution (Barking, Essex : 1987), 2007)
Intra-genus and intra-specific variation and the influence of nitrogen enrichment on net assimilation and stomatal conductance of some annual Trifolium species of Mediterranean dehesa grasslands were assessed under experimental conditions. Also gas exchange rates were compared between some Leguminosae and Poaceae species growing in the field in a dehesa ecosystem in central Spain. The results showed that the previously reported different O3 sensitivity of some Trifolium species growing in pots does not seem to be related to different maximum g(s) values. In addition, no clear differences on gas exchange rates could be attributed to Leguminosae and Poaceae families growing in the field, with intra-genus variation being more important than differences found between families. Further studies are needed to increase the database for developing a flux-based approach for setting O3 critical levels for semi-natural Mediterranean species.
The following values have no corresponding Zotero field: accession-num: 16895740
Keywords: Critical levels; Grasslands; Ozone; Semi-natural vegetation; Stomatal conductance

Monitoring tropospheric ozone impact on plants in natural and urban areas with a Mediterranean climate - Manes, F; Vitale, M; Di Traglia, M (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract To investigate the real linkage and effectiveness of using the AOT40 index and ozone stomatal flux (FO3) in the assessment of physiological alteration/leaf injury on clover clones sensitive to ozone and Quercus ilex plants, two statistical techniques ? Partial Least Squares (PLS) and Neural Net Analysis (NNA) ? were applied. Different results were obtained in relation to the statistical method chosen. Linear methodologies applied to clover highlighted the role of temperature (TEMP) and O3 concentration (O3Mean) in affecting photosynthesis (PHOTO), leaf injury, and stomatal conductance (COND). In Quercus plants, COND was linearly correlated to two environmental variables, TEMP and Vapour Pressure Deficit (VPD), and to two physiological variables, PHOTO and Leaf Transpiration (TRASP), whereas PHOTO was correlated with TEMP, sO3, COND and sub-stomatal CO2/external CO2 ratio (Ci/Ca). These linear relationships were, in part, modified by NNA. In fact, non-linear relationships between environmental variables, and morphological and physiological variables were evident, suggesting caution when risk assessments are made on ozone concentration-based critical levels. Both plant types showed a relationship with FO3 that negatively affected leaf injury and PHOTO in clover and Quercus plants, respectively, suggesting that ozone flux-based critical levels were more effective in linking with leaf injuries or reduction in carbon metabolism.
doi: 10.1080/11263500500333966
Keywords: AOT40; Critical levels; Neural Net Analysis; Ozone; ozone stomatal ﬂux; PLS analysis

Monitoring tropospheric ozone impact on plants in natural and urban areas with a Mediterranean climate - Manes, F.; Vitale, M.; Di Traglia, M. (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2005)
Abstract To investigate the real linkage and effectiveness of using the AOT40 index and ozone stomatal flux (FO3) in the assessment of physiological alteration/leaf injury on clover clones sensitive to ozone and Quercus ilex plants, two statistical techniques ? Partial Least Squares (PLS) and Neural Net Analysis (NNA) ? were applied. Different results were obtained in relation to the statistical method chosen. Linear methodologies applied to clover highlighted the role of temperature (TEMP) and O3 concentration (O3Mean) in affecting photosynthesis (PHOTO), leaf injury, and stomatal conductance (COND). In Quercus plants, COND was linearly correlated to two environmental variables, TEMP and Vapour Pressure Deficit (VPD), and to two physiological variables, PHOTO and Leaf Transpiration (TRASP), whereas PHOTO was correlated with TEMP, sO3, COND and sub-stomatal CO2/external CO2 ratio (Ci/Ca). These linear relationships were, in part, modified by NNA. In fact, non-linear relationships between environmental variables, and morphological and physiological variables were evident, suggesting caution when risk assessments are made on ozone concentration-based critical levels. Both plant types showed a relationship with FO3 that negatively affected leaf injury and PHOTO in clover and Quercus plants, respectively, suggesting that ozone flux-based critical levels were more effective in linking with leaf injuries or reduction in carbon metabolism.
doi: 10.1080/11263500500333966doi: 10.1080/11263500500333966The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: AOT40; Critical levels; Neural Net Analysis; Ozone; ozone stomatal ﬂux; PLS analysis

Assessment of the effects of ozone exposure and plant competition on the reproductive ability of three therophytic clover species from Iberian pastures - Gimeno, B S; Bermejo, V; Sanz, J; de la Torre, D; Gil, J M (Atmospheric Environment, 2004)
Ozone (O3 ) phytototoxicity has been reported on a wide range of crops and wild Central European plant species, however no information has been provided regarding the sensitivity of plant species from dehesa Mediterranean therophytic grasslands in spite of their great plant species richness and the high O3 levels that are recorded in this area. A study was carried out in open-top chambers (OTCs) to assess the effects of O3 and competition on the reproductive ability of three clover species: Trifolium cherleri, Trifolium subterraneum and Trifolium striatum. A phytometer approach was followed, therefore plants of these species were grown in mesoscosms composed of monocultures of four plants of each species, of three plants of each species competing against a Briza maxima individual or of a single plant of each clover species competing with three B. maxima plants. Three O3 treatments were adopted: charcoal ﬁltered air (CFA), non-ﬁltered air (NFA) and non-ﬁltered air supplemented with 40 nl l 1 of O3 (NFA+). The different mesocosms were exposed to the different O3 treatments for 45 days and then they remained in the open. Ozone exposure caused reductions in the ﬂower biomass of the three clover species assessed. In the case of T. cherleri and T. subterraneum this effect was found following their exposure to the different O3 treatments during their vegetative period. An attenuation of these effects was found when the plants remained in the open. Ozone-induced detrimental effects on the seed output of T. striatum were also observed. The ﬂower biomass of the clover plants grown in monocultures was greater than when competing with one or three B. maxima individuals. An increased ﬂower biomass was found in the CFA monoculture mesocosms of T. cherleri when compared with the remaining mesocosms, once the plants were exposed in the open for 60 days. The implications of these effects on the performance of dehesa acid grasslands and for the definition of O3 critical levels is discussed
Keywords: Critical levels; Dehesa; flower biomass; mediterranean grasslands; seed production

Growth response to ozone of annual species from Mediterranean pastures. - Gimeno, B S; Bermejo, V; Sanz, J; de la Torre, D; Elvira, S (Environmental pollution (Barking, Essex : 1987), 2004)
Ozone (O3) phytotoxicity has been reported on a wide range of plant species. However, scarce information has been provided regarding the sensitivity of semi-natural grassland species, especially those from dehesa Mediterranean grasslands, in spite of their great biological diversity and the high O3 levels recorded in the region. A screening study was carried out in open-top chambers (OTCs) to assess the O3-sensitivity of representative therophytes of these ecosystems based on the response of selected growth-related parameters. Three O3 treatments and 3 OTCs per treatment were used. Legume species were very sensitive to O3, because 78% of the tested species showed detrimental effects on their total biomass relative growth rate (RGR) following their exposure to O3. The Trifolium genus was particularly sensitive showing O3-induced adverse effects on most of the assessed parameters. Gramineae plants were less sensitive than Leguminosae species because detrimental effects on total biomass RGR were only observed in 14% of the assessed species. No relationship was found between relative growth rates when growing in clean air and O3 susceptibility. The implications of these effects on the performance of dehesa acidic grasslands and on the definition of ozone critical levels for the protection of semi-natural vegetation are discussed.
Keywords: Critical levels; Dehesa; Relative growth rate; Screening; Therophytes

The relative sensitivity of different mediterranean plant species to ozone exposure - Inclán, R; Ribas, A; Penuelas, J; Gimeno, B S (Water, Air, & Soil Pollution, 1999)
An experimental study was performed in open-top chambers to assess the relative O3-sensitivity of the following Mediterranean woody plants: Quercus ilex ssp. ilex, Quercus ilex ssp. ballota, Olea europaea ssp. sylvestris, Ceratonia siliqua and Arbutus unedo. Assessment of O3 ‘sensitivity’ was based on the development of O3-induced visible injury and the extent of the reduction in relative growth rate induced by O3. Two-year-old seedlings were exposed in open-top chambers to charcoal filtered air (CFA), Non-filtered air (NFA) or Non-filtered air supplied with 40 ppb O3 from 09:00 to 18:00 hours (NFA+40). No clear relationships were found between the development of visible injury and effects on plant growth or accumulated biomass. Olea europea ssp. sylvestris and Quercus ilex ssp. ballota appeared to be the most O3-sensitive tree species screened; a ten month exposure to ambient O3 levels (AOT40 = 12.4 ppm.h) caused reductions in height and/or stem growth. Further research is needed to characterise the physiological, biochemical and anatomical characteristics that may underlie the ‘sensitivity’ of certain Mediterranean species to O3
Keywords: Critical levels; Mediterranean; Ozone; woody species